The Urgency of Risk Mitigation Strategies in Business Agreements - Syahputra, M Arif; Santiago, Faisal (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background: Business agreements are vital in establishing relationships between parties but are susceptible to various legal risks that may disrupt their execution. Such risks include unclear clauses, legal disputes, and unexpected legal changes, which can threaten the sustainability and stability of agreements. Objective: This study aims to emphasize the importance of risk mitigation strategies in business agreements to prevent disputes and ensure fair execution. It seeks to provide insights into effective risk management practices that contribute to the long-term stability of legal relationships. Methods: The research employs a qualitative approach, analyzing existing literature and case studies on risk mitigation techniques. It focuses on the role of protective clauses, dispute resolution mechanisms, and adaptability to evolving legal frameworks. Results: Findings indicate that robust risk mitigation strategies, including clear contract drafting, the use of force majeure clauses, and the implementation of internal legal systems, significantly reduce potential disputes and enhance agreement sustainability. Conclusion: Risk mitigation is an essential aspect of business agreements, requiring proactive measures from drafting to execution. By adopting effective strategies, businesses can foster stability, fairness, and efficiency in their legal relationships.